2015
DOI: 10.1080/14330237.2015.1078093
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and chronotype in adults in Côte d'Ivoire: influence of gender, religion and age

Abstract: This study investigated the sleep-wake rhythm and chronotype of people living in Côte d'Ivoire . We assessed sleep-wake behaviour in 556 adults (336 men, 220 women) between 25 and 54 years (mean: 38 .63) by means of structured interviews . Data were analysed by linear models with sleep wake variables as dependent variables and age, gender, religion and region (urban/rural) as fixed factors controlling for number of working hours and children . Results suggest sleep length not to differ between weekdays and wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, previous research has shown that latitude or the distance to the equator has a significant influence on chronotype because people near the equator live in a stable light–dark cycle throughout the year (Borchers, Ouattara, Vollmer, & Randler, ). Several studies have reported that students in warm climates (Mexico, Colombia, Guatemala, Brazil, Costa Rica, Philippines, and India) perceived themselves to be more morning oriented than students who lived in less warm climates (United States, England, the Netherlands, Russia, Sweden, Germany, and Ireland) (Arrona‐Palacios & Díaz‐Morales, ; Nag & Pradhan, ; Randler, ; Smith et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research has shown that latitude or the distance to the equator has a significant influence on chronotype because people near the equator live in a stable light–dark cycle throughout the year (Borchers, Ouattara, Vollmer, & Randler, ). Several studies have reported that students in warm climates (Mexico, Colombia, Guatemala, Brazil, Costa Rica, Philippines, and India) perceived themselves to be more morning oriented than students who lived in less warm climates (United States, England, the Netherlands, Russia, Sweden, Germany, and Ireland) (Arrona‐Palacios & Díaz‐Morales, ; Nag & Pradhan, ; Randler, ; Smith et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Assume a person, who gets up at 6:00 and goes to bed at 24:00, has the same sleep duration as a person going to bed at 22:00 and waking up at 4:00. Comparable to chronotype, sleep duration decreases with age, and there are gender differences with women sleeping longer than men do (see, e.g., Borchers, Ouattara, Vollmer, & Randler, 2015). Most people sleep longer on weekends compared with weekdays (Roenneberg et al, 2007).…”
Section: Sleep Behaviormentioning
confidence: 99%
“…In all models, age and gender were included as covariates since previous studies report that they are associated with chronotype [ 38 ] and satisfaction with life [ 39 ] as well as with religiosity [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%